PENERAPAN TRI HITA KARANA DALAM HARMONISASI KONSERVASI DAN BUDAYA DI DAYA TARIK WISATA KEBUN RAYA BALI - Wirawan, I Gst Ngurah Putu Dedy; Pendit, I Made Raharja (Jurnal Master Pariwisata (JUMPA); Volume 04, Nomor 01, Juli 2017, 2017)
This article examines the application of Tri Hita Karana (THK) values involving the harmonisation of conservation and culture at the Bali Botanic Garden, Tabanan, Bali. THK is an Hindu beliefs with three main harmonious concepts including harmony among people, harmony with the natural environment and harmony with God. Balinese recognise ecosystem-based nature management, as in the term Tri Mandala, three different level of spaces according to the purpose and benefits of parhyangan (holy place), palemahan (environment) and pawongan (human). These three spaces according to Balinese culture must be harmonious, balanced and preserved in order to support conservation efforts. Combined conservation efforts with cultural values is also a theme that has been utilized by the Bali Botanic Garden in building thematic collections, such as the collection of medicinal plants, traditional ceremonial plants, and ethnobotany artefacts. This collections insight into Balinese cultural conservation supports educational and tourism services at Bali Botanic Garden. The implementation of THK philosophy at Bali Botanic Garden has an important to improves resource efficiency, maintains relationships with the creators, conserves the environment and culture, and maintains harmony in reducing conflict, social imbalances and ensures the sustainability of regional development.